Subjects at-risk for future development of rheumatoid arthritis demonstrate a PAD4-and TLR-dependent enhanced histone H3 citrullination and proinflammatory cytokine production in CD14hi monocytes. Issue 117 (February 2021) - Okamato, Yuko; Ghosh, Tusharkanti; Okamoto, Tsukasa; Schuyler, Ronald P.; Seifert, Jennifer; Charry, Laura Lenis; Visser, Ashley; Feser, Marie; Fleischer, Chelsie; Pedrick, Chong; August, Justin; Moss, Laurakay; et al.
Abstract: The presence of anti-citrullinated protein/peptide antibodies (ACPA) and epitope spreading across the target autoantigens is a unique feature of rheumatoid arthritis (RA). ACPA are present in the peripheral blood for several years prior to the onset of arthritis and clinical classification of RA. ACPA recognize multiple citrullinated proteins, including histone H3 (H3). Intracellular citrullination of H3 in neutrophils and T cells is known to regulate immune cell function by promoting neutrophil extracellular trap formation and citrullinated autoantigen release as well as regulating the Th2/Th17 T cell phenotypic balance. However, the roles of H3 citrullination in other immune cells are not fully elucidated. We aimed to explore H3 citrullination and cytokine/metabolomic signatures in peripheral blood immune cells from subjects prior to and after the onset of RA, at baseline and in response to ex vivo toll-like receptor (TLR) stimulation. Here, we analyzed 13 ACPA (+) subjects without arthritis but at-risk for future development of RA, 14 early RA patients, and 13 healthy controls. We found significantly elevated H3 citrullination in CD14 hi monocytes, as well as CD1c + dendritic cells and CD66 + granulocytes. Unsupervised analysis identified two distinct subsets in CD14 hi monocytes characterized by H3 modification and unique cytokine/metabolomic signatures. CD14 hi monocytes with elevated TLR-stimulated H3 citrullination were significantly increased in ACPA (+) at-risk subjects. These cells were skewed to produce TNFα, MIP1β, IFNα, and partially IL-12. Additionally, they demonstrate peptidyl arginine deiminase 4 (PAD4) mediated upregulation of the glycolytic enzyme PFKFB3. These CD14 hi monocytes with elevated H3 citrullination morphologically formed monocyte extracellular traps (METs). Taken together, dysregulated PAD4-driven cytokine production as well as MET formation in CD14 hi monocytes in ACPA (+) at-risk subjects likely plays an important role in the development of RA via promoting and perpetuating inflammation and generation of citrullinated autoantigens. Highlights: TLR engagement induced histone H3 citrullination in multiple immune cell types. Pro-inflammatory monocytes with histone H3 citrullination were newly identified. Pro-inflammatory monocytes were enhanced in ACPA (+) at-risk via TLR stimulation. PAD4 mediates histone H3 citrullination and cytokine production in monocytes.